HEALTH COUNSELING AND JUVENILE DELINQUENCY AT MADRASAH TSANAWIYAH DUSUN SALAM - Fika Nurul Hidayah; Nurhasanah Nurhasanah (Ann Publisher, 2025)
Background. Adolescents are very vulnerable to various environmental influences, including adolescent associations that can cause delinquency. Factors that drive the rise of deviant behavior include a lack of knowledge about physical and mental health and a lack of social supervision. Aim. The purpose of this community service activity is to provide counseling about the negative impact of juvenile delinquency on physical and mental health. The venue for community service activities with the theme of health counseling and juvenile delinquency at Madrasah Dusun Salam, on February 12, 2024, from 15.00 to 17.00. Methods. The methods used are lectures, interactive discussions, and simulations. Result. This activity showed that participants better understood the importance of maintaining health and the adverse effects of juvenile delinquency. This activity is expected to form positive character of adolescents in the long term. This counseling activity was evaluated with a pre-test score of 50% to a post-test of 80%; there was an increase of around 30%; this shows an increase in adolescent awareness about the impact of juvenile delinquency and health. The active participation of the participants showed that the counseling was going well. Implication. To improve the health of adolescents and prevent deviant behavior, it is hoped that similar activities can be carried out regularly by establishing a youth posyandu.